Home-based Women Workers in Nepal: Their Condition and Contribution - Tuladhar, Reena (Economic Journal of Nepal, 2014)
The main purpose of this paper is to assess the economic contribution of two categories; self-employed and piece rate type of home-based women workers to their household economy. Applying the OLS techniques in a survey data obtained from 375 women home-based workers in Kathmandu valley in 2011 the study found a substantial contribution of home based workers to their household economy. Data analysis showed that income from home-based workers constituted 30 percent of household budget. Background characteristics of home-based workers such as type of work, age, ethnicity, family size, marital status, number of surviving children, place of residence, and educational attainment were found significant predicators.